2019
DOI: 10.1016/j.radonc.2019.07.014
|View full text |Cite
|
Sign up to set email alerts
|

A single-blind, randomised controlled trial of StrataXRT® – A silicone-based film-forming gel dressing for prophylaxis and management of radiation dermatitis in patients with head and neck cancer

Abstract: Aim: Investigate the effects of StrataXRT Ò versus 10% Glycerine (Sorbolene cream) for preventing and managing radiation dermatitis in patients with head and neck cancer receiving radical radiotherapy (!50 Gy) with or without chemotherapy or biotherapy. Methods: A single-blind, randomised controlled, superiority trial was conducted. Patients either received StrataXRT Ò or Sorbolene (usual care). Skin toxicity, pain, itching and skin-related quality of life scores were collected from baseline, and up to four we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…However, a subsequent study found neither a statistical difference for skin reactions nor for moist desquamation rates between treatment and control arms [15,16]. However, another randomized study with head and neck squamous cell cancer (HNSCC) patients investigated a quite similar, film-forming silicone fluid and reported significantly reduced dermatitis rates [33].…”
Section: Discussionmentioning
confidence: 99%
“…However, a subsequent study found neither a statistical difference for skin reactions nor for moist desquamation rates between treatment and control arms [15,16]. However, another randomized study with head and neck squamous cell cancer (HNSCC) patients investigated a quite similar, film-forming silicone fluid and reported significantly reduced dermatitis rates [33].…”
Section: Discussionmentioning
confidence: 99%
“…An Australian trial compared a silicone-film producing gel, StrataXRT, with sorbolene cream for skin reaction severity in 197 head and neck cancer patients in a twoarmed design. 32 The authors showed that patients treated with StrataXRT had a 12% lower risk of developing grade 2 and a 36% lower risk of developing of grade 3 using the CTCAE v4 scale. StrataXRT was applied by the patients twice a day.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that although 3M TM film dressings and corticosteroids were not significantly different vs. control in all respects, 3M TM film dressings may reduce skin itching, while corticosteroids may delay the onset of severe skin inflammation (Shaw et al, 2015). In a singleblind, randomized controlled trial for the prophylactic use of a silicone-based film forming gel dressing (StrataXRT R Stratpharma AG, Basel, Switzerland) in patients with head and neck cancer undergoing radiation therapy, the results show that it is effective for preventing, and delaying the development of grade 2 and 3 skin toxicity (Chan et al, 2019).…”
Section: Radiation Dermatitismentioning
confidence: 99%